Las artes plásticas y la motricidad fina en los niños del nivel inicial II de la Unidad Educativa “José Ingenieros” de la ciudad de Loja, en el período 2021 - 2022 - Masache Quinche, Mónica del Rocío (2022)
Fine motor skills make it possible to carry out movements that require greater precision, that is, each of the planned activities requires proper control of the hands and fingers, such as making smaller movements. The objective of this research was to analyze how the plastic arts help strengthen fine motor skills in children of the initial level II of the José Ingenieros Educational Unit of the City of Loja in the period 2021 - 2022; the research carried out had a mixed approach; with a quasi-experimental design; The methods used were: analytical- synthetic, inductive and deductive. The technique and instruments applied were a survey addressed to the teacher and an assessment scale based on the Initial Education curriculum to a population of 21 children. The results obtained in the initial diagnosis determined that 76% of the children are at the initiated level and in process, due to the fact that they do not comply with the skills of the evaluation scale, presenting difficulties in visual-motor coordination, use of the digital clamp, control of muscle strength and tone, and manipulation of textures, a value that is obtained by adding both indicators. With the execution of the alternative proposal, it was evidenced that it is possible to reduce 38% of difficulty in fine motor skills, obtaining that 38% remain initiated and in process, presenting problems in hand-eye coordination, use of the digital clamp or tripod, control of strength and muscle tone, while 62% of children are in acquired proving that plastic arts activities are effective for the development of motor skills. Concluding that the plastic arts help the development of fine motor skills, considering it extremely important to apply them from an early age in order to enhance their abilities and skills that contribute to the reading-writing process. Keywords: coordination, scribbling, inhibitory brake, techniques, drawing, painting.